The Fourth Industrial Revolution and the Recolonisation of Africa The Coloniality of Data - Benyera, Everisto (Routledge Contemporary Africa, 2021)
This book argues that the fourth industrial revolution, the process of accelerated automation of traditional manufacturing and industrial practices via digital technology, will serve to further marginalise Africa within the international community. In this book, the author argues that the looting of Africa that started with human capital and then natural resources, now continues unabated via data and digital resources looting. Developing on the notion of "Coloniality of Data", the fourth industrial revolutionis postulated as the final phase which will conclude Africa's peregrination towards recolonisation. Global cartels, networks of coloniality, and tech multi-national corporations have turned Big Data into capital, which is left unguarded in Africa as the continent lacks the strong institutions necessary to regulate the mining of data. Written from a decolonial perspective, this book employs three analytical pillars of coloniality of power, knowledge and being. It concludes with an assessment of what could be done to help to turn the fourth industrial revolution from a curse into a resource. Highlighting the crippling continuation of asymmetrical global power relations, this book will be an important read for researchers of African studies, politics and international political economy.